2012
DOI: 10.4142/jvs.2012.13.3.229
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melanocortin (Mc3 and Mc4) antagonists on serotonin-induced food and water intake of broiler cockerels

Abstract: The current study was designed to examine the effects of intracerebroventricular injections of SHU9119 [a nonselective melanocortin receptor (McR) antagonist] and MCL0020 (a selective McR antagonist) on the serotonin-induced eating and drinking responses of broiler cockerels deprived of food for 24 h (FD24). For Experiment 1, the chickens were intracerebroventricularly injected with 2.5, 5, and 10 µg serotonin. In Experiment 2, the chickens received 2 nmol SHU9119 before being injected with 10 µg serotonin. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…For example, in broiler cockerels pre-treatment with melanocortin receptor antagonists attenuates the anorexic effects of icv injections of 5-HT (Zendehdel et al, 2012). In chicks, non-selective CRF receptor antagonists reverse the appetite-suppressing effects of α-MSH (Tachibana et al, 2007) and β-MSH (Kamisoyama et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in broiler cockerels pre-treatment with melanocortin receptor antagonists attenuates the anorexic effects of icv injections of 5-HT (Zendehdel et al, 2012). In chicks, non-selective CRF receptor antagonists reverse the appetite-suppressing effects of α-MSH (Tachibana et al, 2007) and β-MSH (Kamisoyama et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT 2 c expression in POMC neurons might contribute to this effect. Furthermore, it is suggested that the hypophagic effect of 5-HTergic system is mediated via the melanocortin pathway (Nonogaki et al 2008;Zendehdel et al 2012a). The 5HT 2 c receptors affect appetite regulation via several neurotransmitters (Zendehdel et al 2013a(Zendehdel et al , b, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The central 5-HTergic system has a potential effect on food intake. Reportedly the intracerebroventricular (ICV) injection of 5-HT has a hypophagic effect on food intake in chicken (Zendehdel et al 2012a(Zendehdel et al , b, 2013a(Zendehdel et al , b, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these factors play a similar role in trading off sex for ingestive behavior in other model systems. ( McCann and Hansel 1986 ; Wade et al 1991 ; Heisler et al 1994 ; Bruning et al 2000 ; Sullivan et al 2002 ; Benoit et al 2004 ; Woodside et al 2012 ; Zendehdel et al 2012 ; Blevins and Ho 2013 ; Sabatier et al 2013 ; French et al 2014 ; Lopez-Esparza et al 2015 ; Schellekens et al 2015 ; Santoso et al 2017 ; Woodside 2016 ). This initial 1-h kick-off to the symposium suggested many possibilities for linked genes with pleiotropic and/or antagonistic effects that would constrain phenotypic expression and lead to population divergence due to selection for different optima.…”
Section: Moving Beyond Endocrine Secretionsmentioning
confidence: 99%